2024
DOI: 10.1111/epi.17898
|View full text |Cite
|
Sign up to set email alerts
|

Interictal EEG source connectivity to localize the epileptogenic zone in patients with drug‐resistant epilepsy: A machine learning approach

Georgios Ntolkeras,
Navaneethakrishna Makaram,
Matteo Bernabei
et al.

Abstract: ObjectiveTo deconstruct the epileptogenic networks of patients with drug‐resistant epilepsy (DRE) using source functional connectivity (FC) analysis; unveil the FC biomarkers of the epileptogenic zone (EZ); and develop machine learning (ML) models to estimate the EZ using brief interictal electroencephalography (EEG) data.MethodsWe analyzed scalp EEG from 50 patients with DRE who had surgery. We reconstructed the activity (electrical source imaging [ESI]) of virtual sensors (VSs) across the whole cortex and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Thanks to the boom in deep learning, many deep learning models are developed and combined with EEG to detect mental fatigue [151], Parkinson's disease [152], depression [153], schizophrenia [154,155], epilepsy [156][157][158], and neurocognitive disorders [159,160]. In addition to symptom detection, EEG is reported to localize the epileptogenic zone [161,162] and it has the potential to guide the surgery. Kucikiene et al [163] found different EEG features of focal epilepsy and psychogenic nonepileptic seizures.…”
Section: Bioelectrical Sensorsmentioning
confidence: 99%
“…Thanks to the boom in deep learning, many deep learning models are developed and combined with EEG to detect mental fatigue [151], Parkinson's disease [152], depression [153], schizophrenia [154,155], epilepsy [156][157][158], and neurocognitive disorders [159,160]. In addition to symptom detection, EEG is reported to localize the epileptogenic zone [161,162] and it has the potential to guide the surgery. Kucikiene et al [163] found different EEG features of focal epilepsy and psychogenic nonepileptic seizures.…”
Section: Bioelectrical Sensorsmentioning
confidence: 99%